Use of Social Media by the Public Regarding Skin Health: Effects on Dermatological Awareness and Preventive Behaviours - Fortunato Cassalia; Christian Ciolfi; Filippo Scolaro; Andrea Danese; Anna Lunardon; Francesca Caroppo; Anna Belloni Fortina (Acta Dermato-Venereologica, 2023)
Abstract is missing (Short communication)